ANALISIS PELAKSANAAN PEMBELAJARAN BERHITUNG DI TK ASSISI MEDAN - Hilda Trisna Napitu; Nasriah Nasriah (JURNAL TEMATIK, 2019)
This study aims to know how the implementation of learning to count in TK ASSISI Medan. This research is a type of qualitative descriptive research to see the implementation of numeracy learning in TK ASSISI Medan. Retrieval The data source in this study was purposive sampling, namely 3 classes of TK B ASSISI Medan, namely TK B1, TK B3, and TK B5. Data collection techniques used were non-participant observation and documentation. Based on the results of the study showed that seen from the Zoltan P Dienes theory that the implementation of numeracy learning in TK ASSISI Medan still did not involve children in learning, games were still rarely performed and the media and teaching aids were also still underused.